Consumer Cooperation and Its Role in Supplying the Population of Petrograd-Leningrad with Food during the NEP (1921-1928) - E. D. Tverdyukova (Научный диалог)
The role of consumer cooperation in supplying the population of Petrograd-Leningrad with food during the NEP is considered. The novelty of the study is seen in the fact that this problem is studied for the first time on the materials of the largest industrial centre of the country. In the course of the study, the analysis of statistical information was carried out, the materials of office-work and legal documentation and memoirs of contemporaries were involved. Data are given about the location and dynamics of the commercial network, restructuring of Petrograd Union of consumer societies - Leningrad Union of consumer societies. The reasons of prevalence of “private trader” in the food market of the city in the initial period of NEP are investigated. The factors that caused the attractiveness of cooperative shops for citizens, including reduced prices, lending practices, benefits to shareholders are clarified. Social status of buyers, price level, structure of purchases in cooperation and “free” market are analyzed. There are two stages in the supply of the population: until 1926, when the role of a private trader remained significant, and after 1926, when the consumer cooperation began to play a predominant role in providing the city’s workers with products. It is concluded that this was achieved as a result of protectionist activities of the state in relation to the cooperation, the state recognizing the cooperative retail as the main commodity distribution link of Soviet trade.